Pocket companion to Robbins and Cotran pathologic basis of disease - Mitchell, Richard N.; Kumar,Vinay; Abbas, Abul K.; Aster,Jon C. (Elsevier Saunders, 2017)
Complemented by: Robbins and Cotran pathologic basis of disease